Resveratrol relieves myocardial ischemia-reperfusion injury through inhibiting AKT nitration modification - Lei Li; Jiantao Wang; Dandan Zhang; Li Deng; Xudong Zhao; Chunqing Wang; Xianliang Yan; Shuqun Hu (Taylor & Francis Group, 2024)
Objective The aim of this study was to clarify whether Protein kinase B (PKB)/AKT is nitrated in myocardial ischemia and reperfusion injury (MIRI) resveratrol (RSV)'s protective effect during this process.Methods We blocked blood flow of the left coronary artery (LAD) of mice and used H9c2 cells under an oxygen-glucose deprivation (OGD) environment as animal and cell models of MIRI. N-methyl-D-aspartic acid receptor (NMDAR) inhibitor MK801, neuronal nitric oxide synthase (nNOS) inhibitor 7-NI and RSV were used as interventions. Nitration of proteins, infarction area, cardiomyocyte apoptosis and AKT nitration sites were detected during this study.Results During in-vivo study, AKT nitration was induced through the NMDAR/nNOS/peroxynitrite (ONOO-) pathway, leading to decreased phosphorylation of AKT and increased cardiomyocyte apoptosis. AKT nitration was decreased and phosphorylation was elevated when administrated with RSV, MK801 and 7-NI. In in-vitro study, AKT nitration and TUNEL positive cells was elevated when administrated with NO donor H9c2 cells after OGD/R, when administrated with RSV, MK801 and 7-NI, AKT nitration and apoptosis was deceased in H9c2 cells. Mass spectrometry revealed that nitration sites of AKT included 14 Tyrosine residues.Discussion RSV could inhibit AKT nitration and elevated phosphorylation through suppressing NMDAR/nNOS/ONOO- pathway and further reduce the apoptosis of cardiomyocytes in of myocardial I/R.